Prevalence and molecular characterization of Strongyloides stercoralis, Giardia duodenalis, Cryptosporidium spp., and Blastocystis spp. isolates in school children in Cubal, Western Angola - Elena Dacal; José María Saugar; Aida de Lucio; Marta Hernández‐de‐Mingo; Elena Robinson; Pamela C. Köster; María Luisa Aznar; Mateu Espasa; Arlette Ninda; Javier Gandasegui; Elena Sulleiro; Milagros Moreno; et al. (2018)
Human infections by the gastrointestinal helminth Strongyloides stercoralis and the enteric protozoans Giardia duodenalis, Cryptosporidium spp. and Blastocystis spp. are not formally included in the list of 20 neglected tropical diseases prioritised by the World Health Organization. Although largely underdiagnosed and considered of lower public health relevance, these infections have been increasingly demonstrated to cause significant morbidity and even mortality globally, particularly among children living in resource-poor settings. In this cross-sectional survey the prevalence, frequency and molecular diversity of S. stercoralis, G. duodenalis, Cryptosporidium spp. and Blastocystis spp. were investigated in a school children population in the province of Benguela (Angola). A total of 351 stool samples were collected during January to June 2015. The presence of S. stercoralis and G. duodenalis was confirmed by qPCR methods. Giardia duodenalis assemblages and sub-assemblages were determined by multilocus sequence-based genotyping of the glutamate dehydrogenase and β-giardin genes of the parasite. Detection and identification of Cryptosporidium and Blastocystis species and subtypes was carried out by amplification and sequencing of a partial fragment of the small-subunit ribosomal RNA gene of both protozoan. Analyses of risk factors potentially associated with the transmission of these pathogens were also conducted. Prevalences of S. stercoralis, G. duodenalis, Cryptosporidium spp., and Blastocystis spp. were estimated at 21.4% (95% CI: 17.1-25.7%), 37.9% (95% CI: 32.8-43.0%), 2.9% (95% CI: 1.1-4.5%) and 25.6% (95% CI: 21.18-30.2%), respectively. Overall, 64.1% (225/351) of the children were infected by at least one of the pathogens investigated. Sequence analyses of the 28 G. duodenalis isolates that were successfully genotyped allowed the identification of sub-assemblages AI (14.3%), AII (14.3%), BIII (7.1%) and BIV (25.0%). Discordant typing results AII/AIII and BIII/BIV were identified in 7.1% and 14.3% of the isolates, respectively. A total of five additional isolates (17.9%) were identified as assemblage B. Three Cryptosporidium species including C. hominis (70%), C. parvum (20%) and C. canis (10%) were found circulating in the children population under study. A total of 75 Blastocystis isolates were assigned to the subtypes ST1 (30.7%), ST2 (30.7%), ST3 (36.0%), ST5 (1.3%) and ST7 (1.3%), respectively. Children younger than seven years of age had significantly higher risk of infections by protozoan enteropathogens (PRR: 1.35, P < 0.01), whereas being underweight seemed to have a protective effect against these infections (PRR: 0.74, P = 0.005). The burden of disease attributable to human strongyloidiasis, giardiosis, cryptosporidiosis and blastocystosis in Angola is considerably higher than initially estimated in previous surveys. Surveillance and control of these infections should be jointly tackled with formally considered neglected tropical diseases in order to maximize effort and available resources. Our data also demonstrate the added value of using molecular diagnostic methods in high transmission areas.